Ecofriendly and simple synthesis of pyrano[3,2-c]quinolone in water via an efficient one-pot three-component reaction - Radini, Ibrahim Ali; El-Gogary, Sameh Ramadan; Mostafa, Mohamed Sabri; Alnagei, Bander; Mudarbish, Mohammed; Dash, Shadad (European Journal of Chemistry, 2018)
Pyrano[3,2-c]quinolones are commonly found in alkaloids, manifesting diverse biological activities. In this work, 2-amino-6-methyl-5-oxo-4-substituted-5,6-dihydro-4H-pyrano[3,2-c]quinoline-3-carbonitriles and ethyl 2-amino-4-(substituted)-6-methyl-5-oxo-5,6-dihydro-4H-pyrano[3,2-c]quinoline-3-carboxylates have been synthesized efficiently from reaction of 4-hydroxy-1-methylquinolin-2(1H)-one, aldehydes and active methylene nitriles in one-pot three component reaction in aqueous medium, containing catalytic amount of ethanolamine resulting in 70-95% yields.